Analisis Buku Siswa Bahasa Arab Pendekatan Saintifk Kurikulum 2013 Kelas IV Madrasah Ibtidaiyah - Nabila, Syafira Azza; Zannah, Miftahul; Ilahi, Lady Daivi; Salanudin, M. Ilham (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Textbooks or student books are an important component in learning, therefore theymust meet the criteria for textbooks that are suitable for use in accordance withapplicable regulations. And the material contained in the book is material that has agood level of quality. The aim of this research is to determine the level of quality ofgrade IV Arabic books using a scientific approach. The type of method used in thisresearch is a qualitative approach. Based on the results of the analysis, it can be seenwhether there are still errors in terms of content, presentation, language and graphics.And further research is needed regarding this book in the future